PI3K regulates BMAL1/CLOCK-mediated circadian transcription from the Dbp promoter. Issue 6 (2nd June 2016) - Morishita, Yoshikazu; Miura, Daiki; Kida, Satoshi
Abstract: The circadian rhythm generated by circadian clock underlies a molecular mechanism of rhythmic transcriptional regulation by transcription factor BMAL1/CLOCK. Importantly, the circadian clock is coordinated by exogenous cues to accommodate to changes in the external environment. However, the molecular mechanisms by which intracellular-signaling pathways mediate the adjustments of the circadian transcriptional rhythms remain unclear. In this study, we found that pharmacological inhibition or shRNA-mediated knockdown of phosphatidylinositol 3-kinase (PI3K) blocked upregulation of Dbp mRNA induced by serum shock in NIH 3T3 cells. Moreover, the inhibition of PI3K significantly reduced the promoter activity of the Dbp gene, as well as decreased the recruitment of BMAL1/CLOCK to the E-box in the Dbp promoter. Interestingly, the inhibition of PI3K blocked heterodimerization of BMAL1 and CLOCK. Our findings suggest that PI3K signaling plays a modulatory role in the regulation of the transcriptional rhythm of the Dbp gene by targeting BMAL1 and CLOCK. Graphical abstract: : Pharmacological inhibition of PI3K decreased expression levels of Dbp mRNA after the serum shock.